Studies on Urdhwaga Amlapitta (Gastritis) and its Management with Shatavari Ghruta - Sanjore(Naringe), Seema S.; Kharche, G. Y. (Asian Journal of Pharmaceutical Research and Development, 2019)
Amlapitta (Gastritis) is very common ailment found in present time. Amlapitta as per Ayurveda is a disease in which excessive secretion of Amla Guna of Pitta takes place causing symptoms like burning sensation. Though there are many opinions regarding Modern interpretation of Amlapitta, specifically it can be correlate with Gastritis. There are two types of amlapitta mainly Adgoga and Urdhwaga Amlapitta. Type of Amlapitta in which the pitta takes an upward course the patient has mainly vomiting with different colors, burning sensation, headache, loss of appetite, kapha – pittaja jwara, feeling of great heat etc. is called as Urdhwaga Amlapitta. Present study is carried out to assess the efficacy of Shatavari ghruta in Urdgwaga Amlapitta and see the comparative results of Shatavari ghruta and sutshekhar ras and kamdudha rasa in Urdhwaga Amlapitta .For this study 50 patients were selected according to subjective and objective criteria of Urdhwaga Amlapitta and Details of materials and methods, observation and results, statistical analysis, results and discussion of the study with conclusion were described in detail in present article. From this study it can be concluded that Urdhwaga Amlapitta can be managed effectively with Shatavari ghruta as well as with Sutshekhara rasa and Kamdudha rasa as both the groups shows equally effective results statistically.